A Pragmatic Strategy for Monitoring Substance Use and Potential Impacts of Prevention Programming for Local School Districts. Issue 4 (1st October 2016) - Feemster, Kristen G.; Proctor, Steven L.; Hoffmann, Norman G.
Abstract : This study identified peak periods of the onset, prevalence, and correlates of early adolescent substance use, and evaluated the feasibility of implementing a brief student survey at a high school in the southeastern United States. A brief survey was self-administered and 791 students with a mean age of 16.2 years ( SD = 1.24) provided complete data including demographics, past and current substance use, academic performance, absenteeism, and indications of substance dependence. Over half (54.3%) of the current tobacco users reported initiating tobacco use prior to the age of 14 years. Age of tobacco use onset was associated with the use of alcohol and other drugs, indications of substance dependence, absenteeism, and obtaining poor grades. Annual monitoring of substance use rates appears both practical and economical.